Investigating Student Teaching Directors’ Definitions of “Teacher” and Paradigms of Disability in Canadian Teacher Education Programs - Sokal, Laura; Woloshyn, Debra; Wilson, Alina (Alberta Journal of Educational Research, 2022)
Directors of Student Teaching from teacher preparation programs across Canada were surveyed and then interviewed in follow-up focus groups to determine the opportunities and barriers they perceived during processes of placing pre-service teachers with disabilities into practicum settings. These data are interrogated within three theoretical frameworks about disability—the medical model, the social model, and the critical disability theory—to determine whether decision-making by Directors of Student Teaching reflects a predominant paradigm of disability. Deconstructions of the current concept of “teacher” are presented with reference to these three paradigms of disability. Key words: Teacher identity, disability theory, equity. Les directeurs de stages des programmes de formation à l'enseignement de tout le Canada ont été interrogés, puis interviewés dans le cadre de groupes de discussion de suivi, afin de déterminer les possibilités et les obstacles qu'ils perçoivent au cours des processus de placement des enseignants ayant un handicap dans des milieux de stage. Ces données sont étudiées selon trois cadres théoriques sur le handicap - le modèle médical, le modèle social et la théorie critique du handicap - afin de déterminer si la prise de décision des directeurs de stages reflète un paradigme prédominant du handicap. Des déconstructions du concept actuel « d'enseignant » sont présentées en référence à ces trois paradigmes du handicap. Mots clés: identité de l'enseignant, théorie du handicap, équité